Strategi Komunikasi Pemasaran Langen Kusuma dalam Memepertahankan Eksistensi di Masa Pandemi Covid-19. - Ekasari, Intan Desy (The Commercium, 2022)
This study reviews how the marketing communication strategy applied by the Langen Kusuma dance studio hermitage in maintaining its existence during the Covid-19 pandemic. Previous research has proven that a marketing communication strategy is important in supporting the sustainability and existence of the studio in the future. By using case study methods and qualitative research types. In this study, conducting observations and interviews based on data obtained from primary data sources. The results of this study indicate that the Langen Kusuma dance studio applies management and marketing communication strategies in its implementation. Several stages of the management function implemented are planning, organizing, directing, and controlling. The implementation of marketing communication strategies is the main basis for the Langen Kusuma dance studio hermitage to maintain its existence through new activities during the Covid-19 pandemic in the form of advertisements and promotions on social media, holding virtual ganong dance competitions throughout Indonesia, holding final graduation exam performances on the YouTube platform by live streaming and collaborate with television media. The Langen Kusuma dance studio continues to strive to develop new strategies and innovations with the facilities offered and adapt to environmental conditions. Keywords: Marketing Communication Strategy, Langen Kusuma Dance Studio, Existence.